Cancer-Associated Microbiota: From Mechanisms of Disease Causation to Microbiota-Centric Anti-Cancer Approaches - Priyankar Dey; Saumya Ray Chaudhuri (Biology, 2022)
Helicobacter pylori infection is the only well-established bacterial cause of cancer. However, due to the integral role of tissue-resident commensals in maintaining tissue-specific immunometabolic homeostasis, accumulated evidence suggests that an imbalance of tissue-resident microbiota that are otherwise considered as commensals, can also promote various types of cancers. Therefore, the present review discusses compelling evidence linking tissue-resident microbiota (especially gut bacteria) with cancer initiation and progression. Experimental evidence supporting the cancer-causing role of gut commensal through the modulation of host-specific processes (e.g., bile acid metabolism, hormonal effects) or by direct DNA damage and toxicity has been discussed. The opportunistic role of commensal through pathoadaptive mutation and overcoming colonization resistance is discussed, and how chronic inflammation triggered by microbiota could be an intermediate in cancer-causing infections has been discussed. Finally, we discuss microbiota-centric strategies, including fecal microbiota transplantation, proven to be beneficial in preventing and treating cancers. Collectively, this review provides a comprehensive understanding of the role of tissue-resident microbiota, their cancer-promoting potentials, and how beneficial bacteria can be used against cancers.